An Exploratory Study to Identify the Important Factor of The University Website for Admissions During COVID-19 Crisis - Bapat, Gautam; Ravikumar, Chitnis; Shrivallabh, Sane (Journal of Engineering Education Transformations, 2021)
Universities have been using various Communications channels for promoting their brand. Chapleo et al. reported that the segment of Higher Education concerning branding is attracting increasing academic investigation. They also reported that scarce work has been done to investigate if universities are using their websites to proficiently communicate their brands. Universities, having very unique characteristics would be able to communicate very proficiently using their websites (Chapleo et al., 2011). In India, the challenge was particularly tough for enrolling the students in the academic year 2020- 21. The lockdown due to the covid-19 pandemic started in March 2020. All the traditional approaches of University marketers were challenged (Rutter et al., 2017). The role of University websites suddenly became very important concerning reaching the prospective students for the upcoming academic year. Universities started experiencing that the singular approach of their efficiency of delivering academic content digitally was the key factor for the admissions into the academic year 2020-21. An exploratory study was undertaken to investigate how far University websites are efficient in playing an important role in the admission decision-making process. Using the snowball sampling method 700 students, newly admitted into the academic year 2020-21 in various universities in Pune city of Maharashtra were approached. 200 responses were found effective for the study. The hypothesis testing yielded the result that a single or both parents earning family had a close association with the University website’s usability towards admission decisions. The factor analysis was done to investigate the most important component on the University website conceded that faculty profiles and the opportunities for the students concerning employability and placements carried great importance towards admission decisions.